2014
DOI: 10.1016/j.jsv.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Transverse galloping of two-dimensional bodies having a rhombic cross-section

Abstract: a b s t r a c tTransverse galloping is a type of aeroelastic instability characterized by oscillations perpendicular to wind direction, large amplitude and low frequency, which appears in some elastic two-dimensional bluff bodies when they are subjected to an incident flow, provided that the flow velocity exceeds a threshold critical value. Understanding the galloping phenomenon of different cross-sectional geometries is important in a number of engineering applications: for energy harvesting applications the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…The analysis carried by Meseguer et al [105] showed that the more promising bodies were those with isosceles or approximate isosceles cross sections. Based on a rhombic body, Ibarra et al [106] numerically explored the dependency of the instability on a geometrical parameter such as the relative thickness, and the reasons that this crosssection shape, that is generally unstable, shows a small range of relative thickness values where it is stable.…”
Section: Galloping and Vortex-induced Vibrations Of Bluff Bodiesmentioning
confidence: 99%
“…The analysis carried by Meseguer et al [105] showed that the more promising bodies were those with isosceles or approximate isosceles cross sections. Based on a rhombic body, Ibarra et al [106] numerically explored the dependency of the instability on a geometrical parameter such as the relative thickness, and the reasons that this crosssection shape, that is generally unstable, shows a small range of relative thickness values where it is stable.…”
Section: Galloping and Vortex-induced Vibrations Of Bluff Bodiesmentioning
confidence: 99%
“…In these previous tests, pressure distributions were measured, and recorded, at 125 Hz sampling rate during 10 s. This test was used to evaluate the two-dimensional character of the flow acting on the aerofoil, as it was demonstrated from the comparison of measured pressure distributions at different span locations, where no significant differences were found. 31,33 Once a selected model was fixed to the rotating platform, angles of attack were varied from a = 0° to a= 180° at 2° steps, and at each step the six outputs coming from the strain-gauge balance were stored in a PC, as well as the dynamic pressure inside the test chamber. The averaging period used for the mean force coefficients measurements was 10 s at a sampling frequency of 20 Hz.…”
Section: Aerodynamic Coefficients Measurementmentioning
confidence: 99%
“…From the aerodynamic point of view such contact wires can be considered as noncircular cross-section cables [4] exposed to atmospheric turbulent flow. With regard to the characteristics of the wind-induced dynamics of contact-wires, it is known that wind actions on noncircular geometries could eventually trigger aeroelastic instabilities such as galloping phenomena [5][6][7][8]. In fact, Johnson [3] and Scanlon and Oldroyd [9] have extensively reported on the suscep-tibility to suffer undesirable wind-induced phenomena, of the cable system that composes the railway overhead.…”
Section: Introductionmentioning
confidence: 99%